2022
DOI: 10.1371/journal.pone.0266706
|View full text |Cite
|
Sign up to set email alerts
|

Finite-time H∞ synchronization control for coronary artery chaos system with input and state time-varying delays

Abstract: This is the first time for studying the issue of finite-time H∞ synchronization control for the coronary artery chaos system (CACS) with input and state time-varying delays. Feedback control is planned for finite-time of synchronization CACS. By constructing the Lyapunov-Krasovskii functional (LKF) is derived for finite-time stability criteria of CACS with interval and continuous differential time-varying delays. We use Wirtinger-based integral inequality to evaluate the upper bound of the time derivative of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In general, the larger the delay, the greater the instability and volatility of the coronary system. The advantage of the proposed controller is that it can handle a wider delay range than other existing methods, such as Wang et al (2019), Chantawat andBotmart, 2022), andHarshavarthini et al (2020).…”
Section: L2 à L' Performancementioning
confidence: 99%
“…In general, the larger the delay, the greater the instability and volatility of the coronary system. The advantage of the proposed controller is that it can handle a wider delay range than other existing methods, such as Wang et al (2019), Chantawat andBotmart, 2022), andHarshavarthini et al (2020).…”
Section: L2 à L' Performancementioning
confidence: 99%
“…Proof: It has been shown that sliding surfaces Equation ( 11) have finite-time stability, provided that  1 ,  2 are chosen so polynomial of  2 +  2  +  1 = 0 is Hurwitz [39] . For prooving the reaching phase (second part), (10)…”
Section: Designing the Control Inputsmentioning
confidence: 99%
“…These control inputs in the synchronization of the human bones can be considered as the effect of the dose of the chemical drugs. Recently, many control efforts have been made using the synchronization concept in different fields, such as synchronizing communication systems [8,9] , chaotic systems [10,11] , and chemical systems [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…These control inputs in the synchronization of the human bones can be considered as the effect of the dose of the chemical drugs. Recently, many control efforts have been made using the synchronization concept in different fields, such as synchronizing the communication systems [9,10], chaotic systems [11,12], and chemical systems [13,14].…”
Section: Introductionmentioning
confidence: 99%